Pelatihan Penggunaan Microsoft Excel Dalam Membuat Laporan Keuangan di Sapo Rumbia Villa & Cottage - Sembiring, Nita; Sinaga, Mikha; Nainggolan, Yosephine; Noprita Elisabeth Sianturi (LPPM Universitas Potensi Utama, 2023)
Sapo Rumbia Villa and Cottage does not yet have a computerized system for managing daily and monthly financial reports. Sapo Rumbia Villa and Cottage still uses paper media in making financial reports, this causes the financial reports owned by Sapo Rumbia Villa and Cottage to be irregular. Sapo Rumbia Villa and Cottage also does not know how much their monthly expenses and income are. The paper media used to record financial statements is also vulnerable to several things, such as getting wet, torn, dirty, and also burning. The preparation of financial statements is basically used to provide information about the condition of an entity that will be useful to the majority of users of financial statements and to meet the needs of internal and external parties of an entity. At present, financial reports have been compiled in digital form so that it can make it easier for business people to view and check the financial reports of the business units they own. Financial reports made in digital form can be processed easily by users. In addition, financial reports that are created digitally can also be stored properly because they do not require a physical form, can be duplicated quickly, and can be accessed from various gadgets. Based on some of the problems described above, the servant wants to carry out a community service activity at Sapo Rumbia Villa and Cottage. The activities carried out are training on the use of Microsoft Excel in managing financial reports.